(untitled) (Research, Society and Development, 2021)
Mycotoxins are products resulting from fungi metabolism normally present in the environment and which can develop in food. The aim of this study was the fungi quantification, aflatoxin detection and investigation of ergot alkaloids occurrence in pelleted feed for adult equines during storage. The feed samples were collected from three rural properties with equideoculture activity in the city of Teresina, Piauí, Brazil. The results showed that was no significant difference (p<0.05) for the counting of colony-forming units (CFU/g) of filamentous fungi and yeasts in the samples. Aflatoxins B1, B2, G1 and G2 were found in acceptable amounts and the other fungal metabolites: ergometrine, griseofulvin, festuclavin, ergine and lysergol. Concluding, the results of this study demonstrate that amount of filamentous fungi and the water activity present in the original package remain constant after six days of storage. Four types of aflatoxins were found: AFB1, AFB2, AFG1, AFG2 and the Ergot alkaloids: ergine, ergometrine, festuclavine, griseofulvin and lisergol in amounts within acceptable limits. These groups of toxic compounds produced by fungi can be present in equine feed and may lead to a risk to their health.